Pharmacogenomics of intravenous immunoglobulin response in Kawasaki disease - Shrestha, Sadeep; Wiener, Howard W.; Kajimoto, Hidemi; Srinivasasainagendra, Vinodh; Ledee, Dolena; Chowdhury, Sabrina; Cui, Jinhong; Chen, Jake Y.; Beckley, Mikayla A; Padilla, Luz A.; Dahdah, Nagib; Tiwari, Hemant K.; et al. (Frontiers in Immunology, 2024)
Introduction: Kawasaki disease (KD) is, a diffuse vasculitis in children. Response to , shows substantial predilection for coronary artery involvement. hHigh dose intravenous gamma globulin (IVIG), the primary treatment, varies according to genetic background. We sought to identify genetic loci, which associate with treatment response using whole genome sequencing (WGS). represses the KD auto-inflammatory response and reduces coronary artery dilation and aneurysm formation. Susceptibility and treatment response vary substantially by ancestral background.We performed WGS whole genome sequencing (WGS) in 472 KD patients with 305 IVIG responders and 167 non-responders defined by rigorous AHA clinical criteria. We conducted logistic regression models to test additive genetic effect in the entire cohort and in the four subgroups defined by ancestry information markers (Whites, African Americans, Asians, and Hispanics). We performed functional mapping and annotation using FUMA to examine genetic variants and genes that are potentially involved IVIG non-response. Further, we conducted SNP-set [Sequence] Kernel Association Test (SKAT) for all rare and common variants.Results: Of the 43,288,336 SNPs (23,660,970 in intergenic regions, 16,764,594 in introns and 556,814 in the exons) identified, the top ten hits associated with IVIG non-response were in FANK1, MAP2K3:KCNJ12, CA10, FRG1DP, CWH43 regions. When analyzed separately in ancestry-based racial subgroups, SNPs in several novel genes were associated. A total of 23 possible causal genes were pinpointed by positional and chromatin mapping. SKAT analysis demonstrated association in the entire MANIA2, EDN1, SFMBT2, and PPP2R5E genes and segments of CSMD2, LINC01317, HIVEPI, HSP90AB1, and TTLL11 genesConclusions: This WGS study identified multiple predominantly novel understudied genes associated with IVIG response. These data can serve to inform regarding pathogenesis of KD, as well as lay ground work for developing treatment response predictors.